Comparison of Nonexposed Endoscopic Wall-Inversion Surgery with Endoscopic-Navigated Laparoscopic Wedge Resection for Gastric Submucosal Tumours: Results of a Two-Centre Study. (1st July 2019) - Hajer, Jan; Havlůj, Lukáš; Kocián, Petr; Klimbacher, Günther; Shamiyeh, Andreas; Gürlich, Robert; Whitley, Adam
Abstract : Introduction. The aim of this study was to compare the indications, operative details, and clinical outcomes of nonexposed endoscopic wall-inversion surgery with endoscopic-navigated laparoscopic wedge resection of gastric submucosal tumours. Methods . Medical records were reviewed for patients who underwent nonexposed endoscopic wall-inversion surgery (NEWS) at the Faculty Hospital Kralovske Vinohrady and endoscopic-navigated laparoscopic wedge resection (LWR) at the Kepler University Hospital. Demographic, tumour, surgical, perioperative, and follow-up data were collected and compared. Results. Eleven patients underwent NEWS and twelve patients underwent LWR. NEWS was associated with a longer operating time and more frequent suture line bleeding (3 cases in the NEWS group versus 1 case in the LWR group). Negative resection margins were achieved in all NEWS procedures and in 11 of the LWRs. The difference in size between the tumour and the resected specimen was smaller in the NEWS group. Length of hospitalisation was similar between the two groups (NEWS = 6.8 days, LWR = 6.5 days). Follow-up gastroscopies at 12 months postoperatively revealed no signs of recurrence in any of the patients. Conclusion. Nonexposed endoscopic wall-inversion surgery is a new technique for the treatment of gastric tumours. It allows for more precise resections with more frequent achievement of negative resection margins than LWRs. Additionally, it may allow for better preservation of gastric function and limit communication between the gastric lumen and peritoneal cavity. The longer operating time and more frequent complications associated with the NEWS reflects the limited experience with these new techniques.